Better Public Sector Hospitals: Need of the Hour - Haque, Anwar Ul (International Journal of Pathology, 2018)
The public sector hospitals face many problemsespecially in the third world countries. Some of theseproblems directly relate to the prevailing systems ofthe Government and the society rather than to thehospitals per se. As institutions are made by men andnot by cement and bricks, the performance of theinstitutions directly relate to the quality of the men..The fundamental question is: whether country isproducing quality men?